Heavy Metal Pollution and Chemical Profile of Cauvery River Water - Abida Begum; M. Ramaiah; Harikrishna; Irfanulla Khan; K. Veena (E-Journal of Chemistry)
Analysis of water, plankton, fish and sediment reveals that the Cauvery River water in the downstream is contaminated by certain heavy metals. Water samples have high carbonate hardness. Concentrations of all elements and ions increase in the downstream. Main ions are in the following order: Na > HCO3 >Mg > K > Ca> Cl > SO4. Heavy metal concentration in water was Cr >Cu ≈ Mn > Co > Ni > Pb > Zn, in fish muscles Cr > Mn > Cu > Ni > Co > Pb ≈ Zn, in phytoplanktens Co > Zn > Pb > Mn > Cr and in the sediments the heavy metal concentration was Co > Cr > Ni ≈ Cu > Mn > Zn > Pb. Although, the quality of Cauvery River may be classified as very good based on the salt and sodium for irrigation, Zn, Pb and Cr concentration exceeded the upper limit of standards. Metal concentrations in the downstream indicate an increase in the pollution load due to movement of fertilizers, agricultural ashes, industrial effluents and anthropogenic wastes. An immediate attention from the concerned authorities is required in order to protect the river from further pollution.